Pengaruh Perlakuan Panas Terhadap Sifat Mekanis dan Struktur Mikro Paduan Alumunium Silikon - Ahmad Zubair Sultan; Abram Tangkemanda; Irsyad Amru Djafar; Rio Triwanto Rantepadang (Jurnal Teknik Mesin Sinergi, 2019)
: The use of aluminum silicon alloys as automotive components is growing along with the growing desire to reduce the weight of the components used. However, aluminum alloys still have low mechanical properties, so other processes are needed to increase their hardness, one of them by heat treatment process. This alloy material is commonly used for motorcycle piston. This study aims to determine the effect of heat treatment on mechanical properties and microstructure of Aluminum Silicon A383 using the age hardening method with variations in aging temperature and different holding times. The testing of mechanical properties is done by testing the hardness and thermal conductivity. From the testing results, composition of aluminum alloy A383 composed of 73.30% aluminum, 22.08% silicon and highest hardness 105.9HB at an aging temperature 2000C within 30 minutes and the optimal value of the hardness and thermal conductivity of the aging variations performed are at temperature 2000C at holding time 88 minute. As the aging temperature increases, the hardness of aluminum increases and amount of silicon also increase.